Atypical epiretinal tissue in full-thickness macular holes: pathogenic and prognostic significance. Issue 2 (26th April 2018) - Bae, Kunho; Lee, Soo Min; Kang, Se Woong; Kim, Eung Suk; Yu, Seung-Young; Kim, Kyung Tae
Abstract : Background: To elucidate the clinical characteristics of a full-thickness macular hole (FTMH) with atypical epiretinal tissue (AET), and expand the spectrum of pathogenesis of MH. Methods: This study involved 225 consecutive eyes of 211 patients who underwent surgery for an idiopathic FTMH. Eyes were divided into two groups according to the presence of AET. Tomographic features at baseline, closure rate of the MH and visual outcomes were compared between the two groups. Results: AET was detected in 26 (11.6%) among 225 eyes. Overall closure of the MH was noted in 92.3% of eyes with AET and 99.5% of eyes without AET at 12 months postoperatively (p=0.003). At 12 months postoperatively, the mean logarithm of the minimum angle of resolution visual acuity in eyes with and without AET was 0.38 and 0.21, respectively (p=0.046). At baseline, eyes with AET more frequently had splitting of the inner retina but fewer intact photoreceptors compared with eyes without AET (19.2% vs 2.5%, and 57.7% vs 89.9%, p<0.001, respectively). Conclusions: The presence of AET in an FTMH was related to poorer anatomical success and less visual recovery after surgery, suggesting that AET reflects a chronic pathogenic process involving more severe damage to the foveal tissue.